2012
DOI: 10.1016/j.joca.2012.02.635
|View full text |Cite
|
Sign up to set email alerts
|

Side differences of thigh muscle cross-sectional areas and maximal isometric muscle force in bilateral knees with the same radiographic disease stage, but unilateral frequent pain – data from the osteoarthritis initiative

Abstract: Objective To determine whether anatomical thigh muscle cross-sectional areas (MCSAs) and strength differ between osteoarthritis (OA) knees with frequent pain compared with contralateral knees without pain, and to examine the correlation between MCSAs and strength in painful versus painless knees. Methods 48 subjects (31 women; 17 men; age 45–78 years) were drawn from 4796 Osteoarthritis Initiative (OAI) participants, in whom both knees displayed the same radiographic stage (KLG2 or 3), one with frequent pain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
103
4
8

Year Published

2013
2013
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(126 citation statements)
references
References 54 publications
(66 reference statements)
9
103
4
8
Order By: Relevance
“…In this study, we did not detect side differences in thigh muscle anatomic cross-sectional areas (MCSAs) and isometric strength (39). In contrast, a com- parison of participants with unilateral frequent knee pain but concordant radiographic (K/L grade) knee status revealed lower thigh MCSAs and isometric strength in the symptomatic knee (6). However, both studies had lower numbers of participants (Յ48) and there was concern that findings in control knees may be confounded by the contralateral case knees due to the between-knee, withinperson study design and lack of independence of observations in bilateral knees of the same person.…”
Section: Discussioncontrasting
confidence: 67%
See 2 more Smart Citations
“…In this study, we did not detect side differences in thigh muscle anatomic cross-sectional areas (MCSAs) and isometric strength (39). In contrast, a com- parison of participants with unilateral frequent knee pain but concordant radiographic (K/L grade) knee status revealed lower thigh MCSAs and isometric strength in the symptomatic knee (6). However, both studies had lower numbers of participants (Յ48) and there was concern that findings in control knees may be confounded by the contralateral case knees due to the between-knee, withinperson study design and lack of independence of observations in bilateral knees of the same person.…”
Section: Discussioncontrasting
confidence: 67%
“…Baseline measurements for maximum isometric extensor and flexor strength were drawn from the OAI database (clinical data set 0.2.2) (32). These measurements were obtained using the Good Strength Chair (Metitur Oy) (6,33,34), with the participant sitting upright with a fixed pelvis and thigh. The knee was placed in 60°of flexion for testing.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreased quadriceps strength in knee OA has been attributed to both loss of muscle cross-sectional area (43) and reduced ability to activate the muscles (44). In a cohort of 111 subjects taken from a larger RCT, baseline ability to activate quadriceps was examined as one of 9 possible predictors of changes in strength of the muscle following a 6 week exercise program for subjects with knee OA.…”
Section: Muscle Strengthmentioning
confidence: 99%
“…Some studies showed that quadriceps strength was significantly reduced in patients with radiographic knee OA. [37] However, Brandt et al [38] detected reduced muscle strength in patients without radiographic knee OA, and PalmieriSmith et al [39] could not identify any distinction in the quadriceps strength of patients with different radiographic grades according to the KL grading system. In our study, radiological grade was not an influential variable that affected muscle strength in the lower limbs of the OA patients.…”
Section: Discussionmentioning
confidence: 99%